2018
DOI: 10.1002/jcp.26300
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic actions of vitamin D and metformin on skeletal muscles and insulin resistance of type 2 diabetic rats

Abstract: Diabetes Mellitus is a chronic generalized disorder due to insulin insufficiency or resistance. Skeletal muscles represent one of the most important target organs that is affected by insulin signaling. The aim of the current work was to investigate the effect of metformin versus vitamin D (and also simultaneous administration) therapy in type 2 diabetic (T2D) rats on the state of the muscle and insulin sensitivity. Thirty six male rats constituted the animal model and have been divided into five groups: contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 52 publications
4
29
2
Order By: Relevance
“…On the contrary, results herein revealed that both VD3 and LC significantly reduced TGs accumulation in the muscle of VD3-aged and LC-aged rats versus aged ones, with more prominent effect of LC in this respect. Our findings were in parallel with previous studies [1,34,43,59] .…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, results herein revealed that both VD3 and LC significantly reduced TGs accumulation in the muscle of VD3-aged and LC-aged rats versus aged ones, with more prominent effect of LC in this respect. Our findings were in parallel with previous studies [1,34,43,59] .…”
Section: Discussionsupporting
confidence: 93%
“…Vitamin D 3 (VD 3 ) is an essential modulator of calcium and phosphorus metabolism, maintains mucosal barrier homeostasis, and participates in immune regulation . In particular, VD 3 has profound immune‐protective effects in T2DM progression . Recent studies suggest that VD 3 deficiency may play an important role in T2DM and/or CP .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In particular, VD 3 has profound immune-protective effects in T2DM progression. 9 Recent studies suggest that VD 3 deficiency may play an important role in T2DM and/or CP. 10,11 However, there is no conclusive evidence pointing to a correlation between VD 3 deficiency and age, glycemia, or circulatory proinflammatory cytokines in T2DCP.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of metformin on vitamin D levels are sparse. Some data suggest a synergic effect of metformin and vitamin D . Only one cross‐sectional study found a negative association between metformin and vitamin D .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of metformin on vitamin D levels are sparse. Some data suggest a synergic effect of metformin and vitamin D. 23,24 Only one cross-sectional study found a negative association between metformin and vitamin D. 25 In contrast, 2 other studies found that metformin did not affect treatment of vitamin D deficiency with supplementation of vitamin D. 26,27 Therefore, we investigated whether treatment with metformin vs placebo during 52 months affected vitamin D levels in patients in the Hyperinsulinaemia: the Outcome of its Metabolic Effects (HOME) trial.…”
mentioning
confidence: 99%